2013
DOI: 10.5539/ijps.v5n1p11
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Visuospatial Working Memory —Does Emotion Matter?

Abstract: Sex-based differences in visuospatial working memory (VSWM) processing have been documented previously. However, there is a significant lack of empirical data on the gender-related effects on both cognitive load, and the emotional content of spatially-remembered objects in VSWM. In order to explore this issue, 50 young adults (25 males) voluntarily participated in performing a VSWM task with two different levels of cognitive load. Trials included 4 or 6 facial (happy, fearful and neutral faces), or non-facial,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…They found no effect of emotion on spatial WM accuracy, and no difference in performance when the locations were signaled by the presence of faces versus a change in luminance. In contrast, Gonzáles-Garrido and colleagues (2013) asked participants to indicate, in inverse order with respect to presentation order, the locations of four or six faces which had been sequentially and randomly presented each in one of six possible screen regions. This is a more demanding WM task requiring manipulation of the encoded information.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They found no effect of emotion on spatial WM accuracy, and no difference in performance when the locations were signaled by the presence of faces versus a change in luminance. In contrast, Gonzáles-Garrido and colleagues (2013) asked participants to indicate, in inverse order with respect to presentation order, the locations of four or six faces which had been sequentially and randomly presented each in one of six possible screen regions. This is a more demanding WM task requiring manipulation of the encoded information.…”
mentioning
confidence: 99%
“…This is a more demanding WM task requiring manipulation of the encoded information. They found better reverse sequence reports when the locations were occupied by happy faces compared with fearful and neutral faces ( Gonzáles-Garrido et al, 2013 ).…”
mentioning
confidence: 99%
“…Observed differences between males' and females' brain anatomical and functional characteristics could help explain the disparity in performance between the genders on various cognitive tasks (Hill et al, 2014). In general, the gender-related differences include a wide range of processing skills (González-Garrido, Gómez-Velázquez, Sequeira, Ramos-Loyo, & López-Franco, 2013). It has been shown that females recall better the appearance of others better than males (Mast & Hall, 2006) and score higher on tasks involving manipulation of phonological and semantic information, episodic and semantic memory, verbal learning, verbal analytical working memory (WM), object location memory, fine motor skills, perceptual speed and writing skills (Hedges & Nowell, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, previous studies with healthy adults have observed that their performance on a working memory task with emotional stimuli is better when happy faces are shown [7], because this expression is easier to recognize than negative emotions [32]. Therefore, the brain resources involved in its processing are fewer than those needed to maintain and manipulate information in working memory.…”
Section: Behavioral Performancementioning
confidence: 92%
“…Also, they are often hyper-responsive to both angry [3]] [4] and fearful faces [5], and may show deficits in working memory [6]. Considering that memory can be influenced by the emotional content of the stimuli that are to be recalled [7], understanding the relationship between working memory and emotional mechanisms linked to stress suffered early in life requires developing interventions designed to diminish the adverse effects of child maltreatment. In this regard, Cromheeke, Herpoel and Mueller [8] compared the impact of distracting emotional information on working memory performance in women with a history of sexual and physical abuse during childhood/adolescence, individuals reporting non-abuse-related childhood stress, and women without childhood stress.…”
mentioning
confidence: 99%